Synthesis and investigation of spectroelectrochemical properties of peripherally tetra-substituted phthalocyanine bearing 3-(4-{[3-(trifluoromethyl)benzyl]oxy}phenyl)propan-1-ol and its metallo compounds - KOCA, ATIF (SPRINGER, 2018)
In this study, the new compounds; 3-(4-{[3-(trifluoromethyl)benzyl]oxy}phenyl)propan-1-ol 3 was prepared by the reaction of 4-(3-hydroxypropyl)phenol 1 with 1-(bromomethyl)-3-(trifluoromethyl)benzene 2 and 4-[3-(4-{[3 (trifluoromethyl)benzyl]oxy}phenyl)propoxy] phthalonitrile 5 was synthesized by the reaction of 4-nitrophthalonitrile 4 with 3-(4-{[3-(trifluoromethyl)benzyl]oxy}phenyl)propan-1-ol 3. Novel peripherally tetra substituted H2Pc 6, Co(II) 7, Cu(II) 8, Ni(II) 9 and Fe(II) 10 phthalocyanines, which have peripheral positions with 4-[3-(4-{[3 (trifluoromethyl)benzyl]oxy}phenyl)propoxy] groups, were synthesized and all of the new compounds characterized by IR, H-1 NMR, C-13 NMR, UV-Vis, mass spectroscopies and elemental analysis. The electrochemical and spectroelectrochemical investigation of the phthalocyanines carrying 4-[3-(4-{[3 (trifluoromethyl)benzyl]oxy}phenyl)propoxy] groups were studied using various electrochemical techniques in DMF on a glassy carbon electrode. Cyclic voltammetry and square wave voltammetry studies show that the complexes have either metal based or ligand-based diffusion controlled electron transfer properties. To shed more light on the electron-transfer steps of the complexes and assignments of the redox couples were carried out by spectroelectrochemical measurements. The color changes during spectral changes of redox species were recorded with in situ electrocolorimetric measurements. The electrochemical and in situ UV-Vis spectral change of complexes indicated their applicability in the fields of the electrochemical technologies.
Keywords: Phthalocyanine; Synthesis; Electrochemistry; Voltammetry; ELECTROCHEMICAL PROPERTIES; PHOTOCHEMICAL PROPERTIES; IRON(II) PHTHALOCYANINE; OXYGEN REDUCTION; FUNCTIONALIZED GRAPHENE; ZINC PHTHALOCYANINES; METALLOPHTHALOCYANINES; DERIVATIVES; AGGREGATION; MOIETIES